Subungual haematomas: is simple trephining enough?. Issue 4 (July 1998) - Meek, S; White, M
Abstract : OBJECTIVES: To determine the outcome of treating subungual haematomas by simple trephining, in terms of nail appearance and function, and to identify factors associated with a poor outcome. METHODS: Patients with subungual haematomas attending an accident and emergency department over a 12 month period were identified; 5-13 months after injury a telephone and postal survey of patient's assessment of their own outcome was made using a proforma. Outcome was graded according to published criteria. RESULTS: 123 patients with 127 subungual haematomas were identified and 74% were followed up; 85% achieved an "excellent" or "very good" result, with 67% reporting no residual abnormalities. A "poor" outcome occurred in only 2% owing to nail splitting. No correlation was found between adverse outcome and haematoma size, presence of fracture, or infection. CONCLUSIONS: Treatment of subungual haematomas by simple trephining gives an acceptable result in the majority of patients and those with a poor outcome cannot be predicted at presentation. The findings suggest that only simple trephining for symptomatic relief is required for subungual haematomas and that aggressive surgical treatment is unnecessary.